2012
DOI: 10.1111/j.1524-4725.2011.02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Severe Anogenital Acne Inversa (Hidradenitis Suppurativa)

Abstract: Surgery is the cornerstone of treatment for advanced AI. Healing by secondary intention results in significant reduction of complaints and achieves satisfying body contouring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 29 publications
2
36
0
8
Order By: Relevance
“…Wollina et al [138] analyzed the records of patients with anogenital HS from 2000 to 2010 to evaluate the role of surgery in the treatment of severe anogenital HS, and they concluded that surgery is the cornerstone of treatment for advanced forms of HS, and they underlined the importance of secondary intention healing. Watson [139] noted the need for reoperation in approximately 20% of patients with inguinal disease whether they were treated with excision and primary closure or excision and skin grafting.…”
Section: Reconstruction After Radical Wide Excisionmentioning
confidence: 99%
“…Wollina et al [138] analyzed the records of patients with anogenital HS from 2000 to 2010 to evaluate the role of surgery in the treatment of severe anogenital HS, and they concluded that surgery is the cornerstone of treatment for advanced forms of HS, and they underlined the importance of secondary intention healing. Watson [139] noted the need for reoperation in approximately 20% of patients with inguinal disease whether they were treated with excision and primary closure or excision and skin grafting.…”
Section: Reconstruction After Radical Wide Excisionmentioning
confidence: 99%
“…The quality of pain described by patients was hot, burning, pressure, cutting, sharp, taut, splitting, gnawing, sore, throbbing, and aching to sometime during their disease or as a chronic symptom in others. [32]…”
Section: Introductionmentioning
confidence: 99%
“…[326365] In rare cases, however, etanercept can induce AI. [66] In a meta-analysis, 65 studies including 459 patients on TNFαI were evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations